2015
DOI: 10.3892/mmr.2015.3780
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB upregulates ubiquitin C-terminal hydrolase 1 in diseased podocytes in glomerulonephritis

Abstract: Podocyte injury is a pivotal factor during the progression of glomerular diseases. It has been demonstrated that the expression of ubiquitin carboxy-terminal hydrolase L1 (UCH-L1) is increased in injured podocytes in a number of types of glomerulonephritis. However, its mechanism of regulation remains to be elucidated. A previous study by our group suggested that UCH-L1 is a downstream protein of nuclear factor (NF)-κB signaling. In the present study, the involvement of NF-κB in the regulation of the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Liu et al [ 61 ] found that curcumin could prevent glomerular podocyte injury by inhibiting activated Wnt family members and β -catenin downstream effectors in obesity-related glomerular disease model. Zhang et al [ 62 , 63 ] demonstrated that ubiquitin carboxy-terminal hydrolase-1 (UCH-L1) is abnormally expressed in injury podocytes, especially in immune-mediated disease. They also proved that the Wnt/ β -catenin signal pathway is promptly activated in podocyte, coinciding with overexpression of UCH-L1 induced by high glucose meanwhile [ 64 ].…”
Section: Main Signaling Pathways Of Podocyte Injury Mechanism In Dmentioning
confidence: 99%
“…Liu et al [ 61 ] found that curcumin could prevent glomerular podocyte injury by inhibiting activated Wnt family members and β -catenin downstream effectors in obesity-related glomerular disease model. Zhang et al [ 62 , 63 ] demonstrated that ubiquitin carboxy-terminal hydrolase-1 (UCH-L1) is abnormally expressed in injury podocytes, especially in immune-mediated disease. They also proved that the Wnt/ β -catenin signal pathway is promptly activated in podocyte, coinciding with overexpression of UCH-L1 induced by high glucose meanwhile [ 64 ].…”
Section: Main Signaling Pathways Of Podocyte Injury Mechanism In Dmentioning
confidence: 99%
“…52 Another group also found enhanced NF-kB activity in podocytes and other glomerular cells in biopsy specimens from patients with lupus nephritis and IgA nephropathy and patients with nonproliferative membranous nephropathy compared with healthy controls. 53 More direct evidence of podocyte activity was indicated in a study that found that podocyte-specific NEMOdeficient mice have faster recovery from anti-GBMe mediated glomerular injury. 12 Glomerular expression of inflammatory chemokines (CCL2, CCL5, and CCL7) was also reduced in NEMO-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier work had proved that UCH-L1 is expressed aberrantly in the injured podocytes of many nephrites, especially the immunocomplex-mediated nephrites [ 20 , 21 ]. Podocyte injuries are closely related to DN [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%